2021
DOI: 10.3390/vaccines9121451
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Acceptance among Health Science Students in Morocco: A Cross-Sectional Study

Abstract: While students in the health sciences occupy pivotal roles in the Moroccan COVID-19 response and vaccination campaigns, factors associated with COVID-19 vaccine acceptability among students have not been reported. This study aimed to determine the willingness and identify predictive attitudes and beliefs of COVID-19 vaccine acceptance among health science students in Morocco. A cross-sectional, self-administered online questionnaire was conducted among students of the Mohammed VI University of Health Sciences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…And also they have no trust on COVID-19 prevention measures and this lead to a low COVID-19 vaccine acceptance rate in Ethiopia. 42 On the other hand, the result of the current study was higher than a study conducted in Japan (34.6%), 40 the U.S. (29.4%), 40 Morocco (26.9%), 43 Iran (27.9%) 40 and Jordan (36.8). 44 …”
Section: Discussioncontrasting
confidence: 83%
“…And also they have no trust on COVID-19 prevention measures and this lead to a low COVID-19 vaccine acceptance rate in Ethiopia. 42 On the other hand, the result of the current study was higher than a study conducted in Japan (34.6%), 40 the U.S. (29.4%), 40 Morocco (26.9%), 43 Iran (27.9%) 40 and Jordan (36.8). 44 …”
Section: Discussioncontrasting
confidence: 83%
“…However, the same report noted that nearly one household in 10 (11%) would refuse to get vaccinated [6]. More recent studies in Morocco reported low vaccine acceptance rates among health science students (26.9%) [23] and non-health-sciences students (35.3%) [24]. A similar study conducted among healthcare workers found a relatively high vaccination acceptance rate (62.0%).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Main factors associated with COVID-19 vaccine hesitancy by continent and studies. Kanyanda et al25 ; Khalis et al115,116 ; Mejri et al 119 ; Mesele 31 ; Mose 122 ; Omar & Hani 126 ; Saied et al 130 ; Shehata et al 132 ; Solís Arce et al 133 ; Tadele Admasu 134 ; Tagoe et al 135 ; Taye et al 136 ; Uzochukwu et al…”
mentioning
confidence: 99%